After the Euro: National Sovereignty and European Hospitality (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
This paper argues for an original solution of the current political crisis affecting the process of European integration. The underlying idea is that of a double political space: the space of sovereignty and the space of hospitality. While the former is traditionally seen as the political space of the European Nation-States, the latter might be conceived as the political space of a new European Union, where both EU and non-Eu nationals could find their place. This implies that we renounce the category of European citizen and adopt the new political category of European guest instead. Such a solution should be taken into serious consideration if the Eurozone crisis will eventually call into question the European currency union and undermine the project of the “United States of Europe”.